Liminal Zones : Where Lakes End and Rivers Begin - Trevathan, Kim, 1958- (Book collections on Project MUSE., 2013)
After the death of his paddling companion, a German shepherd-labrador retriever mix named Jasper, the author began a series of solitary upstream kayaking quests in search of what he calls "liminal zones," transitional areas where dammed reservoirs give way to the current of the rivers that feed them. For four years he scoured the rivers and lakes of America, where environmentally damaging, and now decaying, man-made structures have transformed the waterways. In this work, he details his upriver adventures, describing the ecological and aesthetic differences between a dammed river and a free-flowing river and exploring the implications of what liminal zones represent - a reassertion of pure, unadulterated nature over engineered bodies of water. The author began by exploring the rivers and creeks of his childhood: the Blood River and Clarks River in western Kentucky. He soon ventured out to the Wolf River, the Big South Fork of the Cumberland, and other waterways in Tennessee. In 2008, he looped around the country with trips to Indiana's Tippecanoe River, Montana's Clearwater River, Oregon's Deschutes and Rogue Rivers, and Colorado's Dolores River, as well as adventures on such southeastern rivers as the Edisto, the Tellico, and the Nantahala. To the author, paddling upstream became a sort of religion, with a vaporous deity that kept him searching. Each excursion yielded something unexpected, from a near-drowning in the Rogue River to a mysterious fog bank that arose across the Nantahala at midday. Throughout this book, the author considers what makes certain places special, why some are set aside and protected, why others are not, and how free-flowing streams remain valuable to our culture, our history, and our physical and spiritual health. This contemplative chronicle of his journeys by water reveals discoveries as varied and complex as the rivers themselves. --